Evaluation of Cell Proliferation and Apoptosis in Placentas of Rats with Severe Diabetes - Rudge, Marilza Vieira Cunha [UNESP]; Costa, Elaine [UNESP]; Barbisan, Luis Fernando [UNESP]; Damasceno, Débora Cristina [UNESP]; Bueno, Aline [UNESP]; Saito, Felipe Hiroshi [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Pinto Rodrigues, Marcela Marcondes [UNESP] (Inst Tecnologia Parana, 2012)
The aim of this work was to analyze the cell proliferation and apoptosis indexes on the 18th and 21st days of pregnancy of diabetic rats and to correlate with maternal glycemia and perinatal outcomes. Placentas from 20 Wistar rats were collected and divided into four experimental groups: control and diabetic of 18 and 21 days of pregnancy. The cell proliferation was analyzed using the PCNA expression and apoptosis by the TUNEL method. It was observed that PCNA and TUNEL indexes decreased from day 18 to 21 of pregnancy in the placentas of diabetic rats and these values were lower than control groups. Diabetic dams presented higher percentage of small for pregnancy age (SPA) fetuses. However, there was no difference between the PCNA and TUNEL indexes in SPA and N-SPA fetuses in all the groups and these indexes were not correlated to maternal glycemic. Thus, placental cell proliferation and apoptosis did not interfere in the intrauterine growth restriction.
Keywords: diabetes; cell proliferation; apoptosis; placenta; rat; IUGR